Evaluation of a superabsorbent wound dressing, patient and clinician perspective: a case series. (2nd March 2020) - Atkin, Leanne; Barrett, Simon; Chadwick, Paul; Callaghan, Rosie; Rippon, Mark G; Rogers, Alan A; Simm, Sue
Abstract : Objective: The primary objective of this study was to evaluate the fluid management capabilities of a superabsorbent wound dressing (Zetuvit Plus Silicone), with secondary objectives related to parameters that support whether the dressing enables undisturbed healing. Method: This study was an open labelled non-comparative study. Patients included in the study were selected by the clinical investigator(s) according to whether the patient required a dressing for the management of moderately to highly exuding wounds. Results: A total of 50 patients were included in the study. Results related to the primary objective demonstrated that the superabsorbent wound dressing was able to absorb all levels of exudate across the range (low to high). At each assessment time point these results show that in 98% of assessments the superabsorbent dressing was rated as 'very good' (91%) or 'good' (7%) at exudate management. Secondary objectives relating to wound bed preparation, healing and management of pain were also positive. Additionally, at the end of each patient treatment, the dressing's fluid management capabilities were rated overall as 'excellent' (100% of cases). There was little pain associated with the wound or at dressing change throughout the study and its flexibility/conformability allowed for comfort and patient satisfaction aligned with increased quality of life. Additionally, inclusion of a silicone adhesive layer allowed painless and atraumatic removal of the dressing, increasing patient comfort, both during wear and at dressing removal, and supported the description of enabling undisturbed wound healing. Conclusion: The superabsorbent wound dressing achieved the primary objective relating to wound exudate management in all the assessments undertaken in this study. In addition, the silicone interface allowed for undisturbed healing as evidenced by little or no adherence of the dressing to underlying tissue, preventing damage to periwound skin. Overall, the superabsorbent wound dressing with the addition of the silicone interface could offer advantages over other superabsorbent polymer dressings (that might adhere to the wound surface) or silicone wound dressings (that might not have the absorbent properties of this type of dressing).